Institutional arrangements and the inflation problem - Brunner, Karl; Meltzer, Allan H. (Amsterdam : New York : North-Holland Pub. Co., 1976)
This book is the third volume of the series, offered as a supplement to the Journal of Monetary Economics, it contains papers presented at the November 1974 conference.
Includes bibliographies pp. 241-243.
usc 05/07/17
Loans
Keywords: Inflation (Finance); Foreign exchange